Barriers and Opportunities to Improve the Implementation of Patient Screening and Linkage to Pre-Exposure Prophylaxis in Primary Care - L. Nacht, Carrie; K. Felner, Jennifer; Muthuramalingam, Sandhya; Towner, William; Ling Grant, Deborah; Martos, Alexander; M. Chang, John; Hechter, Rulin; D. Storholm, Erik (Journal of Clinical Research In HIV AIDS And Prevention, 2022)
Although pre-exposure prophylaxis (PrEP) is highly effective at preventing HIV infection, only around 25% of at-risk individuals in the United States have accessed a prescription. One way to increase PrEP uptake is through the sexual health screening of patients and linkage to PrEP in primary care settings. The objective of this analysis was to assess the barriers and implementation strategies during a screening and linkage to PrEP pilot intervention. Primary care patients were screened for PrEP indication during routine primary care visits. Of the 1,225 individuals screened, 1.8% (n=22) were eligible for PrEP and from those, 77.3% (n=17) attended the specialist appointment and were prescribed PrEP. Primary care patients (n=30) and providers (n=8) then participated in semi-structured interviews assessing their experience with the pilot intervention. Using an applied thematic analytic approach, patients and providers identified barriers and related improvement strategies that could be classified into four main categories: 1) Financial Barriers: Individual- vs. Clinic-level Considerations 2) The Role of Stigma, Discomfort, and Cultural Factors 3) Logistical Hurdles and Streamlining the Intervention, and 4) The Lack of PrEP Knowledge and the Need for Education. Findings support the accepatability and feasibility of screening for PrEP in primary care along with appropriate implementation strategies. This study suggests that because of the high volume of patients seen in primary care, sexual health screenings and linkage to PrEP interventions have the potential to reduce new incident HIV infections among diverse sexual minority men.
Keywords: HIV; PrEP; Primary Care; Qualitative Methods